Interspecies Transformation of Streptomycin Resistance in Oral Streptococci - Davidson, J. R. (1976)
Donor deoxyribonucleic acid extracted from streptomycin-resistant (Str(R)) mutant derivatives of a variety of strains of Streptococcus mutans, S. salivarius, and S. sanguis was used to transform streptomycin resistance into competent S. sanguis strain Challis. Transfer of genetic markers for sorbitol and mannitol fermentation and for extracellular polysaccharide as demonstrated by colonial morphology was not detected in this study. Reciprocal transformation between strain Challis and other oral streptococci could not be demonstrated. Transformation frequencies for Str(R) were relatively efficient among S. sanguis strains, with lower but significant frequencies demonstrated with strain Challis and donor deoxyribonucleic acid derived from other oral streptococci.